Superdog - Hunt, Roderick; Brychta, Alex (Oxford : Oxford University Press, 2003)
"Floppy hates it when the children want him to ne dog of the year. But in a magic adventure he become a big hero."--Back cover.
Keywords: Readers (Elementary)